CANDI TINGKIP DAN LINGKUNGANNYA - Widyawati, Surini; Siregar, Sondang Martini (Siddhayatra, 2018)
Environment and humans are two variables that are interrelated and influence each other,as well as their culture and environment. The environment chosen as a place to live andthe construction of religious buildings need to consider the potential and resources theyhave. In building sacred buildings Hindu-Buddhist religions have special consideration forthe environment. Tingkip Temple is one of the temples in the Musi Rawas area. The purposeof this paper is to determine the relationship between the establishment of Tingkip templebuildings and natural resources in the Musi Rawas area. This research uses qualitativemethods, with inductive reasoning, by collecting library and field data, as well as data processingby conducting environmental analysis. The results of the research show that MusiRawas has natural potential that is suitable as a place for the establishment of sacred buildings,because it has the type of soil that is suitable for organic farming, besides being surroundedby rivers and creeks, and the vegetation around it in the form of agricultural andplantation crops. Musi Rawas natural resource potential affects the establishment of theTingkip Temple.